Graphic organizers as a cognitive strategy to develop vocabulary amongst eighth year b students at Unidad Educativa dr. Manuel Cabrera Lozano of the city of Loja during the 2016-2017 school year. - Correa Mijas, Yuri Silvana (2018)
The aim of the research was to develop the learning of vocabulary in English using graphic organizers as a cognitive strategy with eighth year “B” students at Unidad Educativa Dr. Manuel Agustín Cabrera Lozano of the city of Loja during the 2016-2017 school year. In order to carry out this research work the following methods were used: the analytical-synthetic, the statistical method, the scientific method and the descriptive method. Also, tests and questionnaires were used to diagnose the level of knowledge of English vocabulary, and the field notes to collect data about the behavior and development of the students in each class. The results indicated that students improved significantly their ability to use idioms, cognates, word meaning, collocations and hyponyms. In conclusion, the use of graphic organizers as a cognitive strategy helped overcome the limitations that students had in learning English vocabulary.